Inovasi Pembiayaan Mudharabah Linked Waqf - Novi Febriyanti; Ragil Satria Wicaksana; Fadhilah Nurul Anis; Risma Ruliana; Urwah Al Wusqo; Itam Komalasari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Micro, Small and Medium Enterprises (MSMEs) are buying and selling activities and providing services to the community with the aim of making a profit, but the empowerment of MSMEs is not due to the fact that there are still many obstacles, such as the difficulty for MSMEs to obtain financing facilities from financial institutions, so they are forced to take out loans from loan sharks whose interest rates are high and suffocating. thus causing businesses to go out of business, to overcome this problem MSMEs need Islamic financial institutions with a profit sharing scheme, namely mudharabah contracts or financing/investments which are usually mudharabah products found in Islamic Cooperatives, Indonesian Sharia Bank (BSI), Baitul Maal Wat Tamwil (BMT). The Indonesian Muslim Entrepreneurs Community (KPMI) and the Syirkah Bersama Cooperative (KSBB) are both working together to create a new innovation in the form of Mudharabah Linked Waqf which optimizes and manages cash waqf funds in an organized manner so that it is hoped that it can help MSMEs to develop further.